Pythium species isolated from agricultural waters in Culiacán, Sinaloa - Cárdenas-Rodríguez, Josué; Ayala-Tafoya, Felipe; Yañez-Juarez, Moises Gilberto; López-Orona, Carlos Alfonso; Romero- Gómez, Sergio de Jesús (Ecosistemas y Recursos Agropecuarios, 2022)
Oomycetes are a group of organisms that include destructive genera and species of cultivated and wild plants. In Mexico, especially in the State of Sinaloa, information on these organisms and their presence in surface waters used for agricultural use is scarce. The aim of this study was determining the presence of species of the genus Pythium in waters used for agricultural irrigation in the Culiacán Valley, Sinaloa, Mexico. During September 2018 to January 2019, in 39 sampling points (dams, rivers, canals and water storage ponds for agricultural use), floating traps with pear fruits were placed, used as trap fruits. From the sampled sites, five isolates belonging to the genus Pythium were obtained, were identified by means of  morphological characteristics, extraction and nucleic acid sequencing; in addition, its pathogenicity to plants and fruits of tomato, chili and cucumber was determined. The results obtained determined the presence of Pythium aphanidermatum, P. pachycaule and P. torulosum, which were pathogenic to plants and fruits of tomato, chili and cucumber.